Medicina, Chirurgia e Sanità in Toscana tra '700 e '800 Gli archivi inediti di Pietro Betti, Carlo Burci e Vincenzio Chiarugi - Lippi, Donatella (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2008)
Three Tuscan doctors, and three intriguing professional histories. The inventory of the papers of Pietro Betti, Carlo Burci and Vincenzio Chiarugi has made available an important archive heritage, which goes to supplement the partial knowledge deriving from the biographies and works of these figures who represented the bridge between the enlightened and revolutionary eighteenth century and the following century, taut between the claims of science and political and social influences. A great season for Medicine and Surgery is revisited through the voices of three important exponents of this period of knowledge and action, of a commitment - that is also contemporary - to care, to teaching and to research.